THE EFFECT OF RECLAIM TIRE RUBBER AS ADDITIVE IN MINIMIZING REFLECTIVE CRACKING - HANAA KHALEEL A. AL-BAITI (Diyala Journal of Engineering Sciences, 2010)
The rehabilitation of cracked pavement by overlaying, without any improvement, is rarely a durable solution, as the cracks rapidly propagate through the new asphalt layer. Cracks reflection through the road structure is one of the main causes of premature pavement deterioration which shortens the service life of overlays.